Knowledge On Bitemark Analysis As A Tool In Forensic Odontology Among Undergraduate Students - A.Sai Sanjith, Dr. Abirami Arthanari (Drugs and Cell Therapies in Hematology, 2021)
Introduction: Forensic odontology is the application of dental knowledge to criminals and civil law cases that is dealt with by forensic odontologists. For age determination and identification of unborn individual teeth and bones are most commonly used. For evaluating a child’s growth status, dental age (DA) is used. Aim: The aim of the study is to create Knowledge on bitemark analysis in forensic odontology among undergraduate students. Materials and Method:- A questionnaire was prepared with all the questions regarding this study. This questionnaire was transferred into a survey and the survey was circulated on the online platform among students and faculty of the college. Statistical analysis was done using SPSS software and chi square was done. Results: The present study inferred that most of the people were not aware about bite marks in forensic odontology. 88.7% are aware and 11.3% are not aware of human bite analysis used in forensic odontology. There was no significant association of gender with the knowledge about dental bite marks in forensic odontology (P value > 0.0.5). Conclusion: Undergraduate students had low knowledge about bitemark analysis in forensic odontology. With late advances in research, more target techniques for bite marks examination like salivary DNA recuperation and bacterial genotyping have become pillars of examination in such violations. Further endeavors to lessen subjectivity in standard actual methods are required.